The formation of a good safety culture at enterprise - Järvis, Marina; Tint, Piia (Journal of Business Economics and Management, 2009)
The aim of the study is to show innovative possibilities for improvement of safety culture at enterprises through complex approach to occupational health and safety (OH&S). The knowledge of the leadership and workers in OH&S is not sufficient at present in Estonia, particularly in small and medium‐sized enterprises (the number is 60 000). The small (up to 50 workers) or medium‐sized enterprises (up to 150 workers) have no possibility to hire the working environment specialist who would deal only with OH&S problems. Usually obligations in the field of OH&S in small and medium‐sized enterprises are delegated to one employee in addition to other responsibilities related to personnel, security, fire protection and environmental problems. Therefore, the complex approach to management of OH&S issues is needed in order to create a good safety culture and to achieve positive results in company safety performance. The complex method consists of risk assessment and determination of safety level. The authors offer possible tools ‐ simple computer applications which are available for managers, interviews with employers, employees and occupational health specialists for development and dissemination of safety culture. The opinion of workers and occupational health specialists has been taken into consideration in the planning of improvements of working conditions by the employers. The economic issues of safety and health improvement measures are presented. First Publish Online: 09 Jun 2011